Aplikasi Pemberian Pupuk NPK Phonska dan MSG Terhadap Pertumbuhan dan Hasil Brassica Juncea L. - Juniarny Silvana Suswati Waworuntu (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. This study aims to evaluate the growth and production of mustard greens (Brassica juncea L.) by using a combination of NPK phonska and MSG fertilizers. It was carried out in the experimental garden of Klabat University, Airmadidi from January to May 2020. Using a factorial randomized block design with 2 treatment factors, namely NPK phonska fertilizer with 4 levels (0 g/plant, 1.5 g/plant, 3 g/plant, 4.5 g/plant). plants) and MSG treatment with 3 levels (0 g/liter water, 4 g/liter water, 8 g/liter water). The variables observed were plant height, number of leaves, and plant fresh weight. The treatment of NPK phonska fertilizer had a significant effect on the number of leaves at 33 DAP (Days After Planting), and plant fresh weight. Treatment with MSG had a significant effect on the number of leaves 26 DAP. The best dose of NPK phonska fertilizer for the growth and production of mustard greens is 4.5 g/plant. The best dose for the combination of NPK phonska fertilizer and MSG is 4.5 g/plant and 8 g/liter of water. Abstrak. Penelitian ini bertujuan untuk mengevaluasi pertumbuhan dan hasil Brassica juncea L. dengan perlakuan kombinasi NPK phonska dan MSG. Dilaksanakan di kebun percobaan Universitas Klabat, Airmadidi dari bulan Januari sampai Mei 2020. Menggunakan Rancangan Acak Kelompok Faktorial dengan 2 faktor perlakuan yaitu pupuk NPK phonska dengan 4 taraf (0 gr/tanaman, 1.5 gr/tanaman, 3 gr/tanaman, 4.5 gr/tanaman) dan perlakuan MSG dengan 3 taraf (0 gr/liter air, 4 gr/liter air, 8 gr/liter air). Variabel yang diamati adalah tinggi tanaman, jumlah daun, dan berat segar tanaman. Perlakuan pupuk NPK phonska berpengaruh signifikan terhadap jumlah daun 33 HST (Hari Setelah Tanam), dan berat segar tanaman. Perlakuan pemberian MSG berpengaruh signifikan terhadap jumlah daun 26 HST. Dosis terbaik pupuk NPK phonska untuk pertumbuhan dan hasil Brassica juncea L. adalah 4.5 gr/tanaman. Dosis terbaik kombinasi pupupk NPK phonska dan MSG adalah 4.5 gr/tanaman dan 8 gr/liter air.